The Influence of Facilities, Price, Service Quality and Food Menu Innovation on Consumer Satisfaction at Ayana Sumberjo Buffet Seblak - Irmayani Dalimunthe; Yuniman Zebua; Novrihan Leily Nasution (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the effect of facilities, price, service quality, and menu innovation on consumer satisfaction at Seblak Prasmanan Ayana Sumberjo. This research uses a quantitative approach with a survey method through the distribution of questionnaires to consumers who have made purchases. The data obtained were analyzed using multiple linear regression analysis to determine the relationship between the research variables. The results show that the available facilities provide comfort for consumers while at the business location, thereby increasing their satisfaction. Prices that are considered appropriate with product quality also influence the level of consumer satisfaction. In addition, good service quality such as friendliness, speed, and accuracy in serving consumers can provide a positive experience. Menu innovation that is diverse and attractive is also a factor that can increase consumers' interest in enjoying the products offered. Overall, it can be concluded that facilities, price, service quality, and menu innovation play an important role in increasing consumer satisfaction at Seblak Prasmanan Ayana Sumberjo.